Functional Disability in Psychiatric Patients With Deliberate Self-Harm as Compared to a Clinical Control Group - Nilsson, Magnus; Lundh, Lars-Gunnar; Westrin, Åsa; Westling, Sofie (Frontiers in Psychiatry, 2021)
Background: Deliberate self-harm (DSH) is a common behaviour in psychiatric populations. However, little is known regarding how DSH impacts the daily life. The concept of functional disability, adopted by the World Health Organization (WHO), refers to the impact of disorders on six domains of daily functioning. The aim of the current study was to explore the functional disability of psychiatric patients with DSH as compared to a psychiatric control group. Methods: 32 psychiatric patients with DSH and 31 psychiatric patients without DSH were assessed with regards to demographic information, functional disability, psychiatric illness, DSH, general cognitive functioning and measures of psychopathology. Group comparisons were made by means of t-tests, Mann-Whitney-tests and Chi-square tests. Correlation analyses were done to assess association between measures of psychopathology and functional disability. Results: The results indicated that patients with DSH had a lower ability to self-care as compared to the patients without DSH (p=.001, d= .897). Also, the patients with DSH reported a significantly more number of days when they were totally unable to carry out usual activities in the past month (p=.008, d= .695) and that they were admitted in an inpatient setting significantly more days over the past year compared to the patients without DSH (p<.001, d= .576). The group with DSH was significantly younger (t=3.00, p=.004) and reported significantly more BPD-symptoms (p=.013, d= 0.644) as well as higher current suicidality (p<.001, d= 1.317) compared to the group without DSH. The group with DSH also included a significantly higher number of patients diagnosed with borderline personality disorder (χ2=13.718, p<.001). There were no differences between the groups regarding general cognitive functioning or severity of depression. More research is needed to understand the underlying factors involved.